Foxp3 and IL-10 expression correlates with parasite burden in lesional tissues of post kala azar dermal leishmaniasis (PKDL) patients. - Gajendra Kumar Katara; Nasim Akhtar Ansari; Sandeep Verma; V Ramesh; Poonam Salotra (PLoS Neglected Tropical Diseases, 2011)
BACKGROUND: Post kala-azar dermal leishmaniasis (PKDL), a sequel to visceral leishamaniasis (VL) in 5-15% cases, constitutes a parasite reservoir important in disease transmission. The precise immunological cause of PKDL outcome remains obscure. However, overlapping counter regulatory responses with elevated IFN-γ and IL-10 are reported. METHODOLOGY/PRINCIPAL FINDINGS: Present study deals with ex-vivo mRNA and protein analysis of natural regulatory T cells (nTreg) markers (Foxp3, CD25 and CTLA-4) and IL-10 levels in lesion tissues of PKDL patients at pre and post treatment stages. In addition, correlation of nTreg markers and IL-10 with parasite load in tissue lesions was investigated. mRNA levels of nTreg markers and IL-10 were found significantly elevated in pre-treatment PKDL cases compared to controls (Foxp3, P = 0.0009; CD25 & CTLA-4, P<0.0001; IL-10, P<0.0001), and were restored after treatment. Analysis of nTreg cell markers and IL-10 in different clinical manifestations of disease revealed elevated levels in nodular lesions compared to macules/papules. Further, Foxp3, CD25 and IL-10 mRNA levels directly correlated with parasite load in lesions tissues. CONCLUSION/SIGNIFICANCE: Data demonstrated accumulation of nTreg cells in infected tissue and a correlation of both IL-10 and nTreg levels with parasite burden suggesting their role in disease severity in PKDL.